Role of digital technologies in analysis of choral performance : mechanism of processing sound and musical piece - Prokopov, Sergiy (Universidade Federal de Goiás, 2026)
Achievement of the quality of a choral piece performance is possible provided that the ensemble sound is maintained, the purity of the structure, the expressiveness of timbres, dynamics, and the technical training of the choir members are achieved. The aim of the study is to determine the impact of digital technologies on the improvement of choral performance, considering methods of sound processing and work on a musical piece. The training of choral performers was implemented using digital technologies – Vocalista (for sound processing) and ChoraLine (for work on a musical piece). The research results demonstrated that the students’ choir members were able to achieve a high level of vocal emotionality (4.9 points), an ensemble nature of vocal parts (4.8 points) and performance technique (4.6 points); it has been found that digital technologies had a positive impact on the development of musical ear (4.7 points) and memory (5.0 points). The article’s practical significance lies in the possibility of expanding approaches to teaching choir members using digital technologies.
O papel das tecnologias digitais na análise da performance coral : mecanismo de processamento de som e peça musical
Keywords: Хорове мистецтво, цифрові технології в хоровому мистецтві, музичний перформанс, вокальне мистецтво